Comparing students' performance in final year OSCE: station type and clinical skills assessed - Sim, J.H.; Yang, F.; Anushya, V.; Azura, M.; Vadivelu, J. (2014)
In our instituiton, objective structured clinical examination (OSCE) is a component of the Final MBBS Examination. The purpose of this paper is to analyse students' performance in OSCE. The two objectives were to compare students' performance: (i) in interactive and non-interactive stations, and (ii) in the six clinical skills assessed.